Clinical Benefit of Long-Term Adalimumab Treatment in Patients With Crohn's Disease Following Loss of Response or Intolerance to Infliximab: 96-Week Efficacy Data From GAIN/ADHERE Trials. (25th April 2018) - Panaccione, Remo; Sandborn, William J; D'Haens, Geert; Wolf, Douglas C; Berg, Sofie; Maa, Jen-fue; Petersson, Joel; Robinson, Anne M
Abstract: Background and Aims: In the 4-week GAIN clinical trial, adalimumab was efficacious in inducing remission in patients with moderate-to-severe Crohn's disease [CD] who had prior loss of response/intolerance to infliximab. The efficacy and safety of adalimumab in these patients are reported here for up to 96 weeks or for 3 years, respectively, in the ADHERE open-label extension study. Methods: Patients who completed GAIN could enrol in ADHERE and receive open-label adalimumab 40 mg every other week. Efficacy variables included clinical response (Crohn's Disease Activity Index [CDAI] decrease from baseline ≥70/≥100 points [CR-70/CR-100]) and remission [CDAI<150], steroid discontinuation and fistula remission [absence of drainage]. Data were reported using hybrid non-responder imputation [hNRI], last observation carried forward and as-observed analysis. Subgroup analyses were performed by randomized group in GAIN and by Week 4 efficacy in GAIN. Safety was also assessed. Results: A total of 310 patients from GAIN enrolled in ADHERE. CR-70, CR-100 and remission rates at Week 96 were 39.0%, 35.5%, and 26.5% [hNRI], respectively. Of the patients with CR-70 response or remission at Week 4 of GAIN, 45.5% and 44.4% [hNRI], respectively, maintained the effect at Week 96. Steroid discontinuation and steroid-free remission rates increased from Week 12 to 96 in patients using corticosteroids at GAIN baseline. Conclusions: Long-term adalimumab maintenance therapy led to sustained clinical remission and response, and steroid discontinuation in a considerable proportion of patients with CD previously treated with infliximab. No new safety signals were observed in this patient population.